Hospital ethical climate survey - selected psychometric properties of the scale and results among polish nurses and midwives - Magdalena Dziurka; Patrycja Ozdoba; Linda Olson; Anna Jedynak; Dorota Ozga; Krzysztof Jurek; Beata Dobrowolska (BMC Nursing, 2022)
Abstract Background: The hospital ethical climate affects the quality of nursing care. A positive ethical climate is likely to reduce the proportion of those who consider leaving the profession, so it is necessary to develop tools which will enable assessment and analysis of the hospital ethical climate. The aim of this study was to examine selected psychometric properties of the Polish version of the Hospital Ethical Climate Survey, assess the hospital ethical climate perceived by nurses and midwives from Polish hospitals, and to determine its correlations with job-related variables. Methods: A cross-sectional study among 558 nurses and midwives working in hospitals in Poland. Results: The 21-item model showed acceptable model fitness between the hypothetical model of ethical climate and the data in the study. Five items with low factor loadings were removed from the study. The internal consistency was satisfactory (0.93). The mean score for the overall hospital ethical climate was 3.62. The highest mean score of hospital ethical climate in the present study was found in the ”peers” subscale and the lowest in the ”physicians” subscale. A positive correlation was found between overall hospital ethical climate and respondents’ satisfaction with work, salary, and working time. The hospital ethical climate was associated with problems found in nurses and midwives’ work, such as: limited time for direct face-to-face care, the lack of equipment and resources to provide high-quality health care, strained relations with hospital managers and other health care professionals, limitations to one’s own competences or those of other medical professionals, moral dilemmas related to patient care, the low prestige of nurses’/midwives‘ work, physical and mental burden, and the risk of making a mistake. Conclusion: The Polish 21-item version of the Hospital Ethical Climate Survey is a reliable tool. Correlations revealed that relationships with managers and physicians, and working conditions should be improved in order for the hospital ethical climate to improve.